A densified Cr-doped Al2O3 nanocrystalline coating and its preparation method
Patent Information
- Application Number
- CN202611180941.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-30
AI Technical Summary
然而,Al2O3结晶温度通常高于1000℃,即便在稍低温度下长时间退火也难以结晶,这对常用的不锈钢基体来说不利,易引发相变
[0026](1)本发明提供的致密化Cr掺杂Al2O3纳米晶涂层制备方法,采用磁控溅射制备工艺结合退火和辐照处理,Cr掺杂Al2O3比非晶纯Al2O3的结晶温度低,采用低温退火工艺可有效降低退火过程对基体的不利影响,退火形成纳米晶涂层,其在辐照后变得更致密,涂层内空洞消除、纳米晶的结晶更好,工艺简单、可操作性强。
Smart Images

Figure CN123005293A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of materials technology, specifically relating to a densified Cr-doped Al2O3 nanocrystalline coating and its preparation method. Background Technology
[0002] Lead-cooled fast reactors (LFRs), as one of the important types of fourth-generation nuclear reactors, are characterized by their high power density (up to 400~600 MW / m³). 3 Its closed-loop fuel cycle capability and passive safety characteristics set it apart from other reactor types. The reactor core uses lead-bismuth eutectic (LBE) as a heat transfer coolant, which is crucial for improving inherent safety and power density. However, its long-term corrosiveness poses a challenge to reactor material development. On one hand, LBE reacts with in-core structural materials to form intermetallic compounds, leading to wear and mechanical degradation of the stainless steel matrix. On the other hand, the Pb in LBE... 2+ Bi 3+ Ions can easily penetrate into the interior of stainless steel through material defects, leading to failure risks such as lead embrittlement and bismuth embrittlement. Simultaneously, in-core irradiation damage accelerates these two damage processes. In severe cases, this can lead to core assembly rupture and the release of fission products, seriously threatening the long-term operational safety and lifespan of the reactor (see Ke Hanyin, Liu Jiang, Zhang Ergeng, et al., Research Status and Prospect of Service Damage and Control of Metal Structural Materials in Liquid Lead-Bismuth Corrosion Environment, Hot Working Technology, 2026, 55(07): 195-202). Therefore, developing efficient and stable in-core stainless steel coating protection technology has become a crucial part of the engineering application of lead-cooled fast reactors.
[0003] Among numerous coating protection solutions, alumina (Al2O3) coatings are widely regarded as ideal protective coatings for lead-cooled fast reactor structural materials due to their excellent chemical inertness (does not react significantly with LBE), high temperature resistance (melting point up to 2054℃), and low cost (see P. Lorusso, S. Bassini, A. DelNevo, I. DiPiazza, F. Giannetti, M. Tarantino, M. Utili, GEN-IVLFR development: Status & perspectives, Progress in Nuclear Energy, 2018, 105, 318-331).
[0004] Currently, Al2O3 coating preparation techniques include sol-gel method, magnetron sputtering method, and plasma spraying method, mainly focusing on the preparation of amorphous or low-crystallinity (metastable phases such as γ, θ, and δ phases) Al2O3 coatings. Among them, amorphous Al2O3, as a metastable structure, is prone to structural relaxation or transformation to a crystalline state when operating in a high-temperature environment of around 500℃ in the stack for a long time, leading to a decrease in coating density, stress accumulation, and even cracking (see Yilong Zhong et al., Effect of LBE corrosion on microstructure of amorphous Al2O3 coating by magnetron sputtering, Surface and Coatings Technology, 443, 2022, 128598). More seriously, in the lead-cooled fast reactor environment, the core components are irradiated by high-energy fast neutrons (>1MeV), which causes irradiation defects to form in the amorphous Al2O3 coating. Among them, voids are easy to accumulate and grow and are difficult to heal. Under long-term irradiation, LBE corrosion penetration is likely to occur, resulting in the deterioration of mechanical properties (Yilong Zhong et al., Irradiation effects on microstructure, mechanical properties, and lead-bismuth eutectic corrosion resistance of alumina coating, Journal of Materials Research and Technology, 2023, 25, 2014-2028).
[0005] Theoretically, Al2O3 crystalline coatings treated with high temperatures exhibit superior stability under long-term in-pile irradiation and high-temperature environments. Literature also demonstrates that the formed nanoscale grains and grain boundaries can absorb vacancies and dislocations generated by irradiation. However, Al2O3 crystallization temperatures typically exceed 1000℃, and even prolonged annealing at slightly lower temperatures hinders crystallization. This is detrimental to commonly used stainless steel substrates, as it can easily induce phase transformations. Summary of the Invention
[0006] The purpose of this invention is to solve the above problems and provide a dense Cr-doped Al2O3 nanocrystalline coating and its preparation method. By using low-temperature annealing and irradiation treatment, a high-density nanocrystalline phase is obtained, which weakens the influence of temperature effect on the substrate material and effectively improves the coating's radiation resistance and corrosion resistance.
[0007] To achieve the above objectives, the present invention provides a method for preparing a densified Cr-doped Al2O3 nanocrystalline coating, comprising the following steps:
[0008] S1. Pre-sputtering: Fix the cleaned and dried substrate onto the sample stage in the vacuum chamber, and evacuate the vacuum chamber to a vacuum level below 2 × 10⁻⁶. -3 Pa, the sample stage is heated to 200-300℃, and then evacuated again until the vacuum level is below 2×10. - 3 Pa is used to pre-sputter the AlCr target to complete the target surface cleaning.
[0009] S2, Deposition of coating: A mixture of Ar and O2 with a flow rate ratio of 2:1-4:1 is introduced, and the total gas pressure is 0.4-0.6 Pa. The AlCr target is sputtered using a pulse sputtering power supply with a sputtering pulse current of 100-200 mA, a duty cycle of 25%-50%, and a matching voltage of 300-600 V. Sputtering is stopped when the coating on the substrate surface reaches the preset thickness. The coating is allowed to cool naturally to room temperature to obtain the initial Cr-doped Al2O3 coating.
[0010] S3. Heat treatment: The substrate with the initial coating of Cr-doped Al2O3 is placed in a heating furnace for annealing. Under air or vacuum conditions, the temperature is raised to 600-1000℃ at a heating rate of 15-30℃ / min and held for 1-5 hours. After annealing, a Cr-doped Al2O3 nanocrystalline coating is obtained.
[0011] S4. Irradiation treatment: The Cr-doped Al2O3 nanocrystalline coating is irradiated according to the set irradiation dose. After irradiation, a densified Cr-doped Al2O3 nanocrystalline coating is obtained.
[0012] The above-described method for preparing a densified Cr-doped Al2O3 nanocrystalline coating utilizes Cr atoms in the AlCr target to lower the phase transition energy barrier and increase the diffusion rate of oxygen and aluminum atoms in the Al2O3 coating. This aims to reduce the γ→α phase transition temperature, provide α-Al2O3 heterogeneous nucleation sites, and also serve to pin grain boundaries and refine grains. The percentage of Cr atoms in the AlCr target is preferably 1%-10%, more preferably 2%-9%.
[0013] In the above-described method for preparing a densified Cr-doped Al2O3 nanocrystalline coating, the vacuuming step S1 serves to reduce the influence of other gases in the air. Heating the sample stage enhances the adhesion between the substrate and the coating during deposition. In actual operation, the temperature can be further increased, but this will cause equipment aging and cannot significantly improve the crystallinity.
[0014] Furthermore, the purpose of pre-sputtering is to clean impurities and oxides from the target surface, ensuring consistency in the environment and coating deposition process each time. This invention does not impose special restrictions on pre-sputtering conditions, which can be set according to conventional parameters. Preferably, the pre-sputtering conditions are: Ar gas is introduced as the working gas, with a pressure of 0.3-1.0 Pa, a pulse current of 100-200 mA, a duty cycle of 25%-50%, a matching voltage of 300-600 V, and a pre-sputtering time of 5-10 min.
[0015] In the above-mentioned method for preparing a densified Cr-doped Al2O3 nanocrystalline coating, in step S1, the substrate is stainless steel or a silicon wafer.
[0016] In the above-mentioned method for preparing a densified Cr-doped Al2O3 nanocrystalline coating, in step S2, an Al2O3 coating with a near-stoichiometric ratio can be formed within the range of partial pressure ratio. When the argon-oxygen flow ratio is 3:1, the proportion of aluminum atoms is 41.1%, which is closest to the theoretical value (40%) of the chemical composition of Al2O3. Therefore, the argon-oxygen flow ratio is further preferably 3:1.
[0017] In the above-described method for preparing a densified Cr-doped Al2O3 nanocrystalline coating, the sputtering power supply setting in step S2 is flexible and can be adjusted according to the pulse current, voltage, and duty cycle of the pulse sputtering power supply. In this invention, the sputtering pulse current frequency of the pulse sputtering power supply is 40-60 kHz. Generally, when the pulse current is continuously increased, the voltage may suddenly rise sharply, posing a short circuit risk, which can be mitigated by further reducing the duty cycle. Considering that target surface oxidation poisoning is prone to occur during the Al2O3 coating deposition process, the pulse current and duty cycle should not be set too high outside this range.
[0018] Furthermore, in step S2, the deposition rate under the same sputtering power supply conditions is controlled to achieve a preset thickness for the coating on the substrate surface, with the deposition thickness being proportional to time. During long-term service, the coating may shrink and thin due to increased density; therefore, the prepared coating should not be too thick, typically 1-3 μm being the optimal thickness range, preventing easy corrosion and failure, and also preventing detachment due to structural changes. Therefore, the preferred coating thickness is 1-3 μm.
[0019] In the above-mentioned method for preparing a densified Cr-doped Al2O3 nanocrystalline coating, in step S2, the target-substrate distance between the substrate and the AlCr target is preferably 8-12 cm.
[0020] In the above-mentioned method for preparing a densified Cr-doped Al2O3 nanocrystalline coating, the annealing temperature and time in step S3 can be adjusted. For example, when the annealing temperature is low, the annealing time can be appropriately extended; when the annealing temperature is high, the annealing time should be reduced. When the annealing temperature is 900-1000℃, the holding time should be controlled at around 1 hour; at lower temperatures, it can be increased to 3-5 hours. This method can obtain a Cr-doped Al2O3 nanocrystalline coating. However, if the substrate used has a relatively low phase transformation point, such as stainless steel, excessively high annealing temperatures (above 1000℃) may cause deterioration of the substrate properties. In such cases, the annealing time can be shortened during high-temperature annealing. Furthermore, when the temperature exceeds 1100℃, the coating undergoes volume shrinkage during the Al2O3 transformation from amorphous to γ-phase to α-phase, which can easily cause the coating to detach. Therefore, the annealing temperature should be selected within the range of 600-1000℃, which allows for the formation of nanocrystals without causing significant coating shrinkage and detachment. The heating rate of the furnace is preferably 15-25℃ / min, and the material is allowed to cool naturally to room temperature after annealing. It should also be noted that the Cr-doped Al2O3 nanocrystalline coating is not sensitive to air or vacuum annealing, but if a substrate that is not resistant to air oxidation is used, vacuum annealing can be employed.
[0021] In the above-mentioned method for preparing a densified Cr-doped Al2O3 nanocrystalline coating, step S4 involves irradiation treatment, which causes the atoms in the annealed Cr-doped Al2O3 nanocrystalline coating to migrate and diffuse after dislocation. Furthermore, the Cr atoms lower the diffusion barrier of Al2O3, resulting in higher crystallinity, elimination of voids, and increased density, thereby improving corrosion resistance. The irradiated particles can conventionally be neutrons or ions. The irradiation dose is measured by the commonly used average atomic displacement number (also known as the average atomic displacement number, dpa), which can be set according to conventional parameters, generally requiring a dose above 5 dpa. For light particles such as protons and neutrons, the dose can be reduced to 0.1 dpa; a higher irradiation dose results in better densification. For ions, the irradiation dose is 0.1-20 dpa, and the irradiation time can be controlled according to the irradiated ion beam conditions, generally ranging from 1 to 100 hours. The average atomic displacement number can be calculated using SRIM software, in conjunction with the irradiated particle flux and range. At the same time, the available time can be calculated and controlled based on the irradiated ion beam conditions generated by the equipment (generally, the beam conditions for different elements generated by the accelerator will be different).
[0022] The irradiated particles can be any ions such as hydrogen, helium, gold, and aluminum that produce atomic exposition damage, or they can be uncharged neutrons. Densification is most effective at 10⁻²⁰ dPa. The energy of the irradiated particles is also calculated by the SRIM software based on the coating thickness, generally requiring the maximum coating thickness to be within the particle's range. In comparison, MeV-level heavy ions penetrate the coating to a depth in the μm range, matching the thickness range of the protective coating. Furthermore, heavy ions exhibit higher efficiency and shorter time for exposition damage, making them the preferred irradiated particles for coatings. If a uniform dose evaluation of heavy ions is performed, since the exposition damage effect during the penetration process of heavy ions in materials is similar, only the damage rate differs, the atomic exposition damage dose calculated using SRIM software becomes a reasonable evaluation method for assessing the impact of ions on the atomic cascade collisions of materials. This is also the currently accepted practice for measuring damage. Besides atomic displacement damage dose, the irradiated particles or dose can also be determined based on energy loss. Whether atoms are directly displaced by impact or electrons are ionized to create a thermal effect, theoretically, atoms can leave their original lattice sites, resulting in irradiated enhanced diffusion and thus densifying the coating. However, ions that exert Coulomb interactions on material atoms are more effective than neutrons or even electrons.
[0023] It is important to note that irradiation of neutron particles typically occurs only in reactors. This is because the industry currently uses ion irradiation to approximate neutron irradiation damage, employing the average atomic displacement number as the equivalent damage evaluation criterion. Therefore, it can also be demonstrated that neutrons in a reactor environment can effectively densify coatings.
[0024] The present invention also provides a densified Cr-doped Al2O3 nanocrystalline coating, which is prepared by the above preparation method.
[0025] The present invention provides a densified Cr-doped Al2O3 nanocrystalline coating and its preparation method, which have the following beneficial effects:
[0026] (1) The method for preparing a dense Cr-doped Al2O3 nanocrystalline coating provided by the present invention adopts a magnetron sputtering preparation process combined with annealing and irradiation treatment. Cr-doped Al2O3 has a lower crystallization temperature than amorphous pure Al2O3. The low-temperature annealing process can effectively reduce the adverse effects of the annealing process on the substrate. The nanocrystalline coating is formed by annealing and becomes denser after irradiation. The voids in the coating are eliminated and the crystallization of nanocrystals is better. The process is simple and highly operable.
[0027] (2) During irradiation, Cr-doped Al2O3 nanocrystals grow, and the voids formed during annealing are gradually eliminated by irradiation-enhanced diffusion, resulting in a denser coating. This means that the service performance is not deteriorated by irradiation damage, but rather improved, and is superior to that of undoped Al2O3 coatings. Therefore, this coating has excellent irradiation self-healing properties. Furthermore, neutron irradiation generated during reactor operation can also induce atomic desitu effects, which means that the irradiation treatment in the preparation method of Cr-doped Al2O3 nanocrystal coating can achieve performance improvement during in-reactor service.
[0028] (3) The Cr-doped Al2O3 nanocrystalline coating prepared by the preparation method provided by the present invention can be densified and nanocrystals can grow after irradiation. Some nanocrystals will also grow to form a twin structure with better radiation resistance. This will improve the resistance to lead-bismuth eutectic (LBE) corrosion, which is better than that of amorphous Al2O3 coating. It has excellent radiation resistance and corrosion resistance and has good application prospects in lead-cooled fast reactors. Attached Figure Description
[0029] Figure 1 SEM characterization of the Cr-doped Al2O3 initial coating prepared in Example 3; wherein, (a) is the SEM surface image, (b) is the cross-sectional EDS line scan, and (c) is the cross-sectional EDS point scan and atomic ratio;
[0030] Figure 2 The XRD diffraction peaks of the Cr-doped Al2O3 initial coating prepared in Example 4 after annealing at different temperatures are shown.
[0031] Figure 3 The images show TEM images of the cross-section of the Cr-doped Al2O3 nanocrystalline coating formed after annealing in Example 4; where (a) is the dark field image and EDS line scan of the cross-section, (b) is the bright field image of the cross-section morphology, (c) is the EDS surface scan of the cross-section, and (d) is the SEAD electron diffraction pattern.
[0032] Figure 4 This is an HRTEM image of the Cr-doped Al2O3 nanocrystalline coating formed after annealing in Example 4;
[0033] Figure 5 The images shown are TEM images of the densified Cr-doped Al2O3 nanocrystalline coating prepared in Example 4; where (a) is a TEM image, (b) is a magnified image, (c) is a nanocrystalline HRTEM image, and (d) is a SEAD electron diffraction pattern.
[0034] Figure 6The images are TEM images of the pure Al2O3 nanocrystalline coating prepared in Comparative Example 1 after irradiation; where (a) is a cross-sectional bright-field TEM image, (b) is a HADDF image of another region, and (c) is the corresponding EDS elemental distribution map.
[0035] Figure 7 Images of the densified Cr-doped Al2O3 nanocrystalline coating prepared in Example 3 after LBE etching at 550 °C; where (a) is a surface SEM image and (b) is a cross-sectional EDS elemental distribution. Detailed Implementation
[0036] The technical solutions of various embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are part of the present invention.
[0037] Example 1
[0038] This embodiment provides a method for preparing a densified Cr-doped Al2O3 nanocrystalline coating and the densified Cr-doped Al2O3 nanocrystalline coating prepared by this method. In this embodiment, the percentage of Cr atoms in the AlCr target is 1%. A silicon wafer is used as the substrate. The preparation method specifically includes the following steps:
[0039] S1. Pre-sputtering: Fix the cleaned and dried substrate onto the sample stage in the vacuum chamber, and evacuate the vacuum chamber to a vacuum level below 2 × 10⁻⁶. -3 Pa, the sample stage was heated to 200℃, and then evacuated again until the vacuum level was below 2×10. -3 Pa, Ar gas was introduced as the working gas, and AlCr target was pre-sputtered under the conditions of gas pressure of 0.3 Pa, pulse current of 150 mA, frequency of 60 kHz, duty cycle of 25%, and matching voltage of 300 V to clean impurities and oxides on the target surface. The pre-sputtering time was 10 min.
[0040] S2. Deposition of coating: The target-substrate distance is 8 cm. A mixture of Ar and O2 with a flow rate ratio of 2:1 is introduced. The total gas pressure is 0.4 Pa. The AlCr target is sputtered using a pulse sputtering power supply with a sputtering pulse current of 100 mA, a frequency of 60 kHz, a duty cycle of 25%, and a matching voltage of 350 V. The sputtering time is 20 h. After the coating is allowed to cool naturally to room temperature, the initial coating of Cr-doped Al2O3 is obtained.
[0041] S3. Heat treatment: The substrate with the initial Cr-doped Al2O3 coating deposited is placed in a heating furnace for annealing. Under air conditions, the temperature is raised to 600℃ at a heating rate of 15℃ / min and held for 5 hours. After annealing, a Cr-doped Al2O3 nanocrystalline coating is obtained.
[0042] S4. Irradiation treatment: using 1 MeV of hydrogen ions (H+) + As irradiation particles, Cr-doped Al2O3 nanocrystalline coatings were irradiated with an irradiation dose (dislocation damage) of 0.1 dpa for 100 hours. After irradiation, a densified Cr-doped Al2O3 nanocrystalline coating was obtained.
[0043] Example 2
[0044] This embodiment provides a method for preparing a densified Cr-doped Al2O3 nanocrystalline coating and the densified Cr-doped Al2O3 nanocrystalline coating prepared by this method. In this embodiment, the Cr atomic percentage in the AlCr target is 10%. The substrate is stainless steel. The preparation method specifically includes the following steps:
[0045] S1. Pre-sputtering: Fix the cleaned and dried substrate onto the sample stage inside the vacuum chamber, and evacuate the vacuum chamber to a vacuum level below 1.5 × 10⁻⁶. -3 Pa, the sample stage was heated to 300℃, and then evacuated again until the vacuum level was below 2×10. -3 Pa, Ar gas was introduced as the working gas, and AlCr target was pre-sputtered under the conditions of gas pressure of 0.6 Pa, pulse current of 150 mA, frequency of 40 kHz, duty cycle of 50% and matching voltage of 300 V to clean impurities and oxides on the target surface. The pre-sputtering time was 5 min.
[0046] S2. Deposition of coating: The target-substrate distance is 12 cm. A mixture of Ar and O2 with a flow rate ratio of 4:1 is introduced. The total gas pressure is 0.4 Pa. The AlCr target is sputtered using a pulse sputtering power supply with a sputtering pulse current of 200 mA, a frequency of 40 kHz, a duty cycle of 50%, and a matching voltage of 600 V for 10 h. After the coating is allowed to cool naturally to room temperature, the initial coating of Cr-doped Al2O3 is obtained.
[0047] S3. Heat treatment: The substrate with the initial coating of Cr-doped Al2O3 is placed in a heating furnace for annealing. Under air, the temperature is raised to 1000℃ at a heating rate of 20℃ / min and held for 1h. After annealing, the Cr-doped Al2O3 nanocrystalline coating is obtained.
[0048] S4, Irradiation treatment: using 6MeV aluminum ions (Al) 3+As irradiation particles, Cr-doped Al2O3 nanocrystalline coatings were irradiated with an irradiation dose (ex-situ damage) of 20 dpa for 20 hours. After irradiation, a densified Cr-doped Al2O3 nanocrystalline coating was obtained.
[0049] Example 3
[0050] This embodiment provides a method for preparing a densified Cr-doped Al2O3 nanocrystalline coating and the densified Cr-doped Al2O3 nanocrystalline coating prepared by this method. In this embodiment, the percentage of Cr atoms in the AlCr target is 5%. A silicon wafer is used as the substrate. The preparation method specifically includes the following steps:
[0051] S1. Pre-sputtering: Fix the cleaned and dried substrate onto the sample stage in the vacuum chamber, and evacuate the vacuum chamber to a vacuum level below 2 × 10⁻⁶. -3 Pa, the sample stage was heated to 200℃, and then evacuated again until the vacuum level was below 2×10. -3 Pa, Ar gas was introduced as the working gas, and AlCr target was pre-sputtered under the conditions of gas pressure of 0.5 Pa, pulse current of 150 mA, frequency of 40 kHz, duty cycle of 25%, and matching voltage of 300 V to clean impurities and oxides on the target surface. The pre-sputtering time was 7 min.
[0052] S2. Deposition of coating: The target-substrate distance is 8 cm. A mixture of Ar and O2 with a flow rate ratio of 3:1 is introduced. The total gas pressure is 0.5 Pa. The AlCr target is sputtered using a pulsed sputtering power supply with a sputtering pulse current of 150 mA, a frequency of 40 kHz, a duty cycle of 25%, and a matching voltage of 500 V. The sputtering time is 8 h. After the coating is allowed to cool naturally to room temperature, the initial coating of Cr-doped Al2O3 is obtained.
[0053] S3. Heat treatment: The substrate with the initial coating of Cr-doped Al2O3 was placed in a heating furnace for annealing. Under air, the temperature was raised to 900℃ at a heating rate of 25℃ / min and held for 1h. After annealing, the Cr-doped Al2O3 nanocrystalline coating was obtained.
[0054] S4. Irradiation treatment: using 6 MeV gold ions (Au) 2+ The Cr-doped Al2O3 nanocrystalline coating was irradiated with 10 dpa as the irradiation particle and the irradiation time was 2 hours. After irradiation, a densified Cr-doped Al2O3 nanocrystalline coating was obtained.
[0055] Example 4
[0056] This embodiment provides a method for preparing a densified Cr-doped Al2O3 nanocrystalline coating and the densified Cr-doped Al2O3 nanocrystalline coating prepared by this method. In this embodiment, the Cr atomic percentage in the AlCr target is 5%. The substrate is stainless steel. The preparation method specifically includes the following steps:
[0057] S1. Pre-sputtering: Fix the cleaned and dried substrate onto the sample stage in the vacuum chamber, and evacuate the vacuum chamber to a vacuum level below 2 × 10⁻⁶. -3 Pa, the sample stage was heated to 200℃, and then evacuated again until the vacuum level was below 2×10. -3 Pa, Ar gas was introduced as the working gas, and AlCr target was pre-sputtered under the conditions of gas pressure of 0.5 Pa, pulse current of 150 mA, frequency of 40 kHz, duty cycle of 25%, and matching voltage of 300 V to clean impurities and oxides on the target surface. The pre-sputtering time was 7 min.
[0058] S2. Deposition of coating: The target-substrate distance is 8 cm. A mixture of Ar and O2 with a flow rate ratio of 3:1 is introduced. The total gas pressure is 0.5 Pa. The AlCr target is sputtered using a pulse sputtering power supply with a sputtering pulse current of 150 mA, a frequency of 40 kHz, a duty cycle of 25%, and a matching voltage of 500 V. The sputtering time is 8 h. After the coating is allowed to cool naturally to room temperature, the initial coating of Cr-doped Al2O3 is obtained.
[0059] S3. Heat treatment: Six substrates with Cr-doped Al2O3 initial coatings were placed in a heating furnace for annealing. In an air environment, the temperature was raised to 600℃, 800℃, 900℃, 1000℃, 1100℃ and 1200℃ respectively at a heating rate of 25℃ / min. The substrates were then held at the corresponding temperatures for 1 hour. After annealing, Cr-doped Al2O3 nanocrystalline coatings were obtained.
[0060] S4. Irradiation treatment: using 6 MeV gold ions (Au) 2+ The Cr-doped Al2O3 nanocrystalline coating was irradiated with 20 dpa as the irradiation particle and the irradiation time was 5 hours. After irradiation, a dense Cr-doped Al2O3 nanocrystalline coating was obtained.
[0061] Comparative Example 1
[0062] This embodiment provides a method for preparing a pure Al2O3 nanocrystalline coating and the pure Al2O3 nanocrystalline coating prepared by this method. The substrate is stainless steel. The preparation method specifically includes the following steps:
[0063] S1. Pre-sputtering: Fix the cleaned and dried substrate onto the sample stage in the vacuum chamber, and evacuate the vacuum chamber to a vacuum level below 2 × 10⁻⁶. -3 Pa, the sample stage was heated to 200℃, and then evacuated again until the vacuum level was below 2×10. -3 Pa, Ar gas was introduced as the working gas, and the Al target was pre-sputtered under the conditions of gas pressure of 0.5 Pa, pulse current of 150 mA, frequency of 40 kHz, duty cycle of 25%, and matching voltage of 300 V to clean impurities and oxides on the target surface. The pre-sputtering time was 7 min.
[0064] S2. Deposition of coating: The target-substrate distance is 8 cm. A mixture of Ar and O2 with a flow rate ratio of 3:1 is introduced. The total gas pressure is 0.5 Pa. The Al target is sputtered using a pulse sputtering power supply with a sputtering pulse current of 150 mA, a frequency of 40 kHz, a duty cycle of 25%, and a matching voltage of 500 V. The sputtering time is 5 h. After the coating is allowed to cool naturally to room temperature, a pure Al2O3 initial coating is obtained.
[0065] S3. Heat treatment: The substrate with the initial pure Al2O3 coating deposited is placed in a heating furnace for annealing. Under air conditions, the temperature is raised to 900℃ at a heating rate of 25℃ / min and held for 1 hour. After annealing, a pure Al2O3 nanocrystalline coating is obtained.
[0066] S4. Irradiation treatment: using 6 MeV gold ions (Au) 2+ The pure Al2O3 nanocrystalline coating was irradiated with irradiation particles. The irradiation dose (dislocation damage) of the coating was 20 dpa, and the irradiation time was 5 hours. After irradiation, a densified pure Al2O3 nanocrystalline coating was obtained.
[0067] The following section analyzes the structure and composition of the dense Cr-doped Al2O3 nanocrystalline coatings prepared in Examples 3, 4, and Comparative Example 1.
[0068] (I) SEM analysis of sedimentary Al2O3
[0069] Figure 1SEM characterization of the initial Cr-doped Al2O3 coating prepared in Example 3: (a) SEM surface image, (b) cross-sectional EDS line scan, (c) cross-sectional EDS point scan and atomic ratio. It can be seen that the surface of the deposited coating is uniform and without obvious defects; Si diffuses into the coating, possibly due to continuous heating during the preparation process; an Al-Si-O transition layer is formed at the coating-substrate interface, which can further improve the adhesion between the coating and the substrate; the coating thickness is approximately 1.3 μm, the Al:Cr atomic ratio is approximately 96.33:3.67, and the O:(Al+Cr) ratio in the coating is 1.62, which is basically consistent with the elemental stoichiometry of the Al2O3 coating within the error range. The Al:Cr atomic ratio in the coating deviates somewhat from the 95:5 ratio of the target material, which may be due to the higher sputtering yield of Al compared to Cr, or it may be due to the limitations of SEM-EDS testing itself in element detection.
[0070] (II) XRD analysis after annealing
[0071] Figure 2 These are the XRD diffraction peaks of the Cr-doped Al2O3 initial coating prepared in Example 4 after annealing at different temperatures. It can be seen that the deposited coating is amorphous, exhibiting γ-phase Al2O3 diffraction peaks above 600 °C. At annealing temperature of 900 °C, a peak representing the α-phase Al2O3 (PDF-74-1081) was first observed. At annealing temperature of 1000 °C, several peaks matching the α-phase were observed. At 1100 °C, a distinct α-phase was observed, while the γ-phase disappeared. This means that at annealing temperatures of 900-1000 °C, a mixed nanocrystalline structure of α-phase and γ-phase Al2O3 was formed in the Cr-doped Al2O3 coating. This indicates that Cr doping significantly reduces the nucleation temperature of Al2O3, promoting the formation of both γ-phase and α-phase Al2O3.
[0072] (III) TEM analysis after annealing
[0073] Figure 3 The following are TEM images of the cross-section of the Cr-doped Al2O3 nanocrystalline coating formed after annealing at 900°C for 1 hour in air in Example 4: (a) dark field image and EDS line scan of the cross-section, (b) bright field image of the cross-section morphology, (c) EDS surface scan of the cross-section, and (d) SAED electron diffraction pattern. Figure 3 In (a) the high-angle annular dark field image (HAADF) mode, the image contrast is related to the atomic number of the material, combined with Figure 3Images (a) and (b) show that some relatively large voids were observed in the top region of the coating (appearing as dark contrast in HAADF and bright contrast in bright-field images), and a small number of tiny voids were also found inside the Al2O3 coating. This may be related to the volume shrinkage effect and internal stress release caused by the transformation of the amorphous component of Al2O3 to the crystalline phase during annealing. Bright-field images show that although some voids exist, the overall morphology of the coating is relatively uniform, exhibiting typical polycrystalline diffraction contrast, especially in the region near the substrate. Figure 3 The selected area electron diffraction pattern of the coating region in (d) proves that the coating has a polycrystalline structure, but the diffuse diffraction ring in the center indicates that there are also some amorphous phases in the coating. Figure 3 (c) is an EDS scan of the cross-section after annealing. It can be seen that Al, O, and Cr elements in the coating remain uniformly distributed after annealing, indicating that Cr element is uniformly doped in the Al2O3 coating. Furthermore, Figure 3 (c) shows that Cr diffused from the stainless steel substrate into the coating near the interface and segregated in the interface region, which was due to the diffusion process being promoted by annealing.
[0074] (iv) HRTEM analysis after annealing
[0075] Figure 4 This is an HRTEM image of the cross-section of the Cr-doped Al2O3 nanocrystalline coating formed in Example 4 after annealing at 900°C for 1 hour. Figure 4 The atomic phase analysis revealed that the size of Al2O3 nanocrystals is below 10 nm, and the grains are arranged randomly.
[0076] (v) TEM analysis after annealing and re-irradiation
[0077] Figure 5 This is a TEM image of the dense Cr-doped Al2O3 nanocrystalline coating obtained after irradiation with 20 dpa Au ions in Example 4. Figure 6 This is a TEM image of the pure Al2O3 nanocrystalline coating obtained after irradiation with 20 dpa Au ions in Comparative Example 1.
[0078] Figure 5 The cross-sectional morphology in (a) and (b) shows that the coating thickness is approximately 0.95 μm, which is smaller compared to the deposited and annealed coatings; the grain size is significantly larger, and the density is also increased; the Al2O3 coating becomes denser, and no voids were found. (c) and (d) show the grain morphology and electron diffraction pattern after irradiation, indicating that the formed Al2O3 nanocrystals have better crystallinity, and the diffraction spots are clearer than those of the unirradiated ones. Furthermore, some Al2O3 nanocrystals exhibit twinning characteristics, providing a better coating grain structure for radiation resistance. Figure 6 As can be seen from (a)-(c), the undoped Al2O3 nanocrystalline coating has a large number of voids and large grains. This result indicates that the structure of the undoped Al2O3 coating is severely degraded after annealing and irradiation at 900 °C, and a large number of pores are retained inside.
[0079] Figure 5 and Figure 6 This demonstrates that the dense Cr-doped Al2O3 nanocrystalline coating prepared by the method of this invention has good radiation resistance, and the coating becomes denser and has better crystallinity after irradiation, exhibiting the characteristic of self-healing after irradiation.
[0080] (vi) SEM analysis after annealing-irradiation-corrosion
[0081] The image of the dense Cr-doped Al₂O₃ nanocrystalline coating obtained by irradiation with 20 dpa Au ions in Example 4 after 500 hours of lead-bismuth eutectic (LBE, lead 44.5 wt%, bismuth 55.5%) etching at 550 °C is shown below. Figure 7 As shown; (a) is the surface SEM image, and (b) is the cross-sectional EDS elemental distribution. First, the surface is basically smooth, with no obvious corrosion pits or grains except for residual Pb and Bi. Second, the cross-sectional elemental distribution also showed no Pb and Bi penetration into the coating. Figure 6 It can be seen that the dense Cr-doped Al2O3 nanocrystalline coating prepared by the preparation method provided by the present invention not only has good radiation resistance, but also good corrosion resistance.
[0082] In summary, the method for preparing a densified Cr-doped Al2O3 nanocrystalline coating provided by this invention is convenient and effective. The prepared coating exhibits a nanocrystalline structure and has excellent radiation resistance and high-temperature resistance to lead-bismuth eutectic (LBE) corrosion, making it applicable to lead-cooled fast reactor environments.
[0083] Those skilled in the art will recognize that the embodiments described herein are intended to help the reader understand the principles of the invention, and should be understood that the scope of protection of the invention is not limited to such specific statements and embodiments. Those skilled in the art can make various other specific modifications and combinations based on the technical teachings disclosed in this invention without departing from the spirit of the invention, and these modifications and combinations are still within the scope of protection of this invention.
Claims
1. A method for preparing a densified Cr-doped Al2O3 nanocrystalline coating, characterized in that... Includes the following steps: S1. Pre-sputtering: Fix the cleaned and dried substrate onto the sample stage in the vacuum chamber, and evacuate the vacuum chamber to a vacuum level below 2 × 10⁻⁶. -3 Pa, the sample stage is heated to 200-300℃, and then evacuated again until the vacuum level is below 2×10. -3 Pa is used to pre-sputter the AlCr target to complete the target surface cleaning. S2, Deposition of coating: A mixture of Ar and O2 with a flow rate ratio of 2:1-4:1 is introduced, and the total gas pressure is 0.4-0.6 Pa. The AlCr target is sputtered using a pulse sputtering power supply with a sputtering pulse current of 100-200 mA, a duty cycle of 25%-50%, and a matching voltage of 300-600 V. Sputtering is stopped when the coating on the substrate surface reaches the preset thickness. The coating is allowed to cool naturally to room temperature to obtain the initial Cr-doped Al2O3 coating. S3. Heat treatment: The substrate with the initial coating of Cr-doped Al2O3 is placed in a heating furnace for annealing. Under air or vacuum conditions, the temperature is raised to 600-1000℃ at a heating rate of 15-30℃ / min and held for 1-5 hours. After annealing, a Cr-doped Al2O3 nanocrystalline coating is obtained. S4. Irradiation treatment: The Cr-doped Al2O3 nanocrystalline coating is irradiated according to the set irradiation dose. After irradiation, a densified Cr-doped Al2O3 nanocrystalline coating is obtained.
2. The method for preparing a densified Cr-doped Al2O3 nanocrystalline coating according to claim 1, characterized in that: The percentage of Cr atoms in the AlCr target is 1%-10%.
3. The method for preparing a densified Cr-doped Al2O3 nanocrystalline coating according to claim 1, characterized in that: In step S1, the pre-sputtering conditions are as follows: Ar gas is introduced as the working gas, the gas pressure is 0.3-1.0 Pa, the pulse current is 100-200 mA, the duty cycle is 25%-50%, the matching voltage is 300-600 V, and the pre-sputtering time is 5-10 min.
4. The method for preparing a densified Cr-doped Al2O3 nanocrystalline coating according to claim 1, characterized in that: In step S1, the substrate is stainless steel or silicon wafer.
5. The method for preparing a densified Cr-doped Al2O3 nanocrystalline coating according to claim 1, characterized in that: In step S2, the coating thickness is 1-3 μm.
6. The method for preparing a densified Cr-doped Al2O3 nanocrystalline coating according to claim 1, characterized in that: In step S2, the target-substrate distance between the substrate and the AlCr target is 8-12 cm.
7. The method for preparing a densified Cr-doped Al2O3 nanocrystalline coating according to claim 1, characterized in that: In step S3, the heating furnace has a heating rate of 15-25℃ / min, and after annealing, it is naturally cooled to room temperature.
8. The method for preparing a densified Cr-doped Al2O3 nanocrystalline coating according to claim 1, characterized in that: In step S4, the irradiation dose is 0.1-20 dpa.
9. The method for preparing a densified Cr-doped Al2O3 nanocrystalline coating according to claim 8, characterized in that: In step S4, the irradiation dose is 10-20 dpa.
10. A densified Cr-doped Al2O3 nanocrystalline coating prepared by any one of the preparation methods described in claims 1-8.
